DOI: 10.18174/563317
|View full text |Cite
|
Sign up to set email alerts
|

From seed to seedling - damping-off tolerance in Spinacia oleracea L

Abstract: Table of contents Chapter 1. General introduction Chapter 2. Sensitivity of spinach seed germination to moisture is driven by oxygen availability and influenced by seed size and pericarp Chapter 3. Evaluation of damping-off tolerance in spinach cultivars in field soils and in a standardised lab assay with Pythium ultimum Chapter 4. Rate of seedling emergence is not the only driver of pre-emergence damping-off tolerance in spinach Chapter 5. Higher seed maturity levels, darker pericarp, and smaller seed size re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 148 publications
0
1
0
Order By: Relevance
“…Although the effect may depend on the crop, the pathogen pressure and other field conditions, this demonstrated the potential advantage of high vigour seeds for farming. A study with spinach (Spinacia oleracea) seeds showed that smaller seeds with a thinner pericarp are less sensitive to high soil moisture conditions that limit oxygen diffusion [34], whereas less mature spinach seeds are more sensitive to the soil borne pathogen Pythium ultimum [35]. In the frame of the LIVESEED project we studied the effect of vigour on biotic stress tolerance using carrot seeds and the pathogen Alternaria radicina, which can cause seedling 'damping-off' by infecting and damaging the root system.…”
Section: Seed Vigourmentioning
confidence: 99%
“…Although the effect may depend on the crop, the pathogen pressure and other field conditions, this demonstrated the potential advantage of high vigour seeds for farming. A study with spinach (Spinacia oleracea) seeds showed that smaller seeds with a thinner pericarp are less sensitive to high soil moisture conditions that limit oxygen diffusion [34], whereas less mature spinach seeds are more sensitive to the soil borne pathogen Pythium ultimum [35]. In the frame of the LIVESEED project we studied the effect of vigour on biotic stress tolerance using carrot seeds and the pathogen Alternaria radicina, which can cause seedling 'damping-off' by infecting and damaging the root system.…”
Section: Seed Vigourmentioning
confidence: 99%